2022
DOI: 10.3389/fpsyt.2021.752539
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Profiles in a Sample of Moroccan High School Students: Comparison Before and During the COVID-19 Pandemic

Abstract: BackgroundAdolescent high school students may be particularly susceptible to suffering from the effect of isolation, physical distancing restrictions, and school closures imposed during the COVID-19 (Corona Virus Disease 2019) pandemic. Given the biological and psychological changes that occur during this period of development, adolescents' experiences of these pandemic measures could significantly threaten their mental health and cause long-term consequences.AimThe main objectives of the study were to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 113 publications
(136 reference statements)
3
15
0
Order By: Relevance
“…In addition to these recent studies on adult health, many researchers have investigated the effects of COVID-19 restrictions on children and adolescents, as they are more vulnerable to environmental stress and often have a more limited understanding of stressful situations and fewer strategies than adults to cope with sudden changes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. For instance, Meherali et al [ 19 ] reviewed 18 studies with a total number of 20,150 children and adolescents from five countries, (i.e., Australia, Canada, China, Italy, and the USA) and concluded that COVID-19 restrictions had a great impact on the mental health of children and adolescents, causing anxiety, depression, disturbances in sleep and appetite, and impairment of social interactions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to these recent studies on adult health, many researchers have investigated the effects of COVID-19 restrictions on children and adolescents, as they are more vulnerable to environmental stress and often have a more limited understanding of stressful situations and fewer strategies than adults to cope with sudden changes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. For instance, Meherali et al [ 19 ] reviewed 18 studies with a total number of 20,150 children and adolescents from five countries, (i.e., Australia, Canada, China, Italy, and the USA) and concluded that COVID-19 restrictions had a great impact on the mental health of children and adolescents, causing anxiety, depression, disturbances in sleep and appetite, and impairment of social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, the prevalence of depression in adolescents during the COVID-19 pandemic is higher than it was before the pandemic [ 8 , 20 , 22 , 23 , 36 , 37 ]. For instance, Serra et al [ 37 ] reported that approximately 24% of children and adolescents in Italy reported typical depressive symptoms, such as depressed mood, physical symptoms, and negative self-esteem.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations